Menière’s Disease and Caloric Stimulation: Some News from an Old Test - Cerchiai, Niccolò (J Int Adv Otol, 2019)
OBJECTIVES: The aim of the present study was to improve the instrumental diagnosis of assessing Menière’s disease (MD) if the frequency and slow-phase velocity (SPV) of the thermally induced nystagmus analyzed through the caloric vestibular test (CVT) showed different alterations in relationship with an increasing severity of the cochlear involvement. MATERIALS AND METHODS: The study retrospectively analyzed the CVT results of 72 patients affected by unilateral “definite MD” according to the 2015 Barany Society Diagnostic Criteria and treated only conservatively. RESULTS: There were 7 (9.72%) patients in stage 1, 27 (37.50%) in stage 2, 35 (48.61%) in stage 3, and 3 (4.16%) in stage 4. The canal paresis (CP) calculated through the frequency of the thermally induced nystagmus on the affected side increased in more severe stages (p=0.033). Conversely, the CP calculated through the SPV was not significantly different among the stages showing abnormal values even in the early phases of the disease (71% in stage 1, 81% in stage 2, 91% in stage 3, and 100% in stage 4), exclusively on the affected side. CONCLUSION: Abnormalities of the thermally induced nystagmus on the affected side characterize most patients with MD, but only “SPV” alterations are common in the early stages. An increasing severity of the cochlear involvement progressively reflects also on the ”frequency” parameter. Detecting a dissociation between these two parameters could represent an instrumental marker of the early forms of MD.